A new silver cluster that emits bright-blue phosphorescence. Issue 16 (30th January 2020) - Yang, Jin-Sen; Zhang, Miao-Miao; Han, Zhen; Li, Hai-Yang; Li, Lin-Ke; Dong, Xi-Yan; Zang, Shuang-Quan; Mak, Thomas C. W.
Abstract : A new stable hexanuclear silver(i ) cluster features brightly blue phosphorescence at room temperature, which is integrated with yellow phosphors (YAG:Ce 3+ ) to white-light-emission film and demonstrates interesting mechanoresponsive luminescence. Abstract : A new hexanuclear silver(i ) cluster (NC-Ag6 ) that emits bright-blue phosphoresce with a lifetime of 22.4 μs and a quantum yield (QY) of 22% under ambient conditions was synthesized. A film combining NC-Ag6 with yellow cerium(iii )-doped yttrium aluminum garnet phosphors (YAG:Ce 3+ ) displays "chameleon"-like emission (including white), which is related to excitation-dependent Förster resonance energy transfer (FRET) between dual phosphors. The mechanoresponsive luminescence colour of this silver cluster ranges from blue to green virtually without loss of QY.